Outcome Mapping as a monitoring and evaluation tool in the Ecohealth Field Building Initiative Leadership Initiative (FBLI) in Southeast Asia - Giang Thi Huong Pham; Tung Xuan Dinh; Mallee, H.; Hung Nguyen-Viet (Veterinary Public Health Centre for Asia Pacific, 2013)
Monitoring and Evaluation (M&E) activity is essential in any project management and helps to verify if a project has met the planned activities, outputs and outcomes. We present here M&E framework for the Ecohealth Field Building Initiative Leadership Initiative (FBLI) in South East Asia using Outcome Harvesting as a tool. Outcome Harvesting as a variation of Outcome Mapping - a M&E concept focusing on one specific type of result: outcomes as behavioral change - has been used to monitor and evaluate the achievements of hundreds of networks, non-governmental organizations, research centers, think tanks, and community-based organizations around the world. We will describe the process of monitoring used in the FBLI program i.e. how proposed tools such as detailed monitoring and the quarterly bulletin, the self-reflection tool, as well as Outcome Harvesting are integrated to monitor and evaluate the expected outputs as well as what the program’s varying hopes and expectations are, laid out in the project proposal as what the program would love to see, like to see and expect to see in the field of Ecohealth building in South East Asia. The five year FBLI program, funded by the IDRC, is a research project aimed at positing Ecohealth as a sustainable dynamic field in the region. The three major components of the project, namely capacity building, knowledge translation, and research, are the progress markers that can be considered as indicators of behavioral change in boundary partners as well as desired outcomes in the Ecohealth field. These provide a basis for monitoring the progress and outcomes of the program.